Identification Early Warning Signs of Suicidal Behavior Among Adolescents - Suherman Suherman; Hema Malini; Renidayati Renidayati (Faculty of Nursing, Universitas Andalas, 2018)
Background: Increasing number of suicide cases, especially in adolescents, becomes problems that require serious treatment. Adolescence is a period of transition and hormonal development that can affect the emotions or mood. It is known that before attempting suicide, there are signs of language or linguistic such as verbal and nonverbal as an indication of the suicidal behavior action. Purpose: This systematic review aims to identify these signs based on the results of several studies. It is expected that the result can be used as basic data to identify signs and symptoms. Methods: Systematic literature searching was conducted in consultation with nursing librarians and linguistic, using Science Direct, Biomed Central and PubMed databases. The keywords used were: warning and suicide; verbal and non-verbal language of suicide and suicide in adolescents. Results: 12 articles related to the teenagers in suicide attempts keywords were found. Conclusion: Suicide signs revealed through verbal and non-verbal languages such as statements or communication that indicated desire to physically harm himself. This warning signs may include suicide notes, indirect threats, and immediate threats.